2019
DOI: 10.1620/tjem.249.203
|View full text |Cite
|
Sign up to set email alerts
|

GPI-80 as a Useful Index for Myeloid Cell Heterogeneity and a Potential Prognostic Biomarker for Metastatic Renal Cell Carcinoma

Abstract: Myeloid-derived suppressor cells (MDSCs), which include neutrophilic MDSCs and monocytic MDSCs, exhibit high immunosuppressive activity. Glycosylphosphatidylinositol-anchored 80 kD protein (GPI-80) is selectively expressed on mature neutrophils in healthy individuals. Increased GPI-80 expression on monocytes and variations in GPI-80 expression on neutrophils indicate the appearance of MDSCs in the peripheral blood of cancer patients. However, it is still unclear whether GPI-80 expression on myeloid cells, neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Notably, elevated GPI-80 expression has been reported in activated neutrophils [13]. We further demonstrated that increased expression of the coefficient of variation (CV) of GPI-80 (GPI-80 CV) on neutrophilic cells (CD16 hi cells) indicates unusual differentiation of neutrophils related to MDSC functions [10,12].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Notably, elevated GPI-80 expression has been reported in activated neutrophils [13]. We further demonstrated that increased expression of the coefficient of variation (CV) of GPI-80 (GPI-80 CV) on neutrophilic cells (CD16 hi cells) indicates unusual differentiation of neutrophils related to MDSC functions [10,12].…”
Section: Introductionmentioning
confidence: 64%
“…Previously, we demonstrated a method for the identification of myeloid cells from peripheral blood via staining with the myeloid cell marker CD33 and the neutrophil maturation marker CD16 (FcγRIII) in cases of RCC [9][10][11]. We revealed that the expression of CD16 and the TGFβ precursor molecule latency-associated peptide-1 (LAP-1) on monocytic cells (CD33 hi cells) is an indicator of MDSC status, as these parameters are involved in the suppression of antitumor immunity in patients with RCC [12]. Moreover, we identified that increased expression of glycosylphosphatidylinositol-anchored 80 kD protein (GPI-80) is an indicator of neutrophil maturation [10].…”
Section: Introductionmentioning
confidence: 99%
“…The contraction and fluctuation of cell clusters are useful for categorizing the signal characteristics. Previously, we demonstrated that CV of the neutrophil surface molecule GPI-80 was useful for the detection of neutrophil differentiation and heterogeneity (Kato et al, 2019;Takeda et al, 2016). These observations suggest that the categorization will be not only used for phosphorylated molecules but also cell surface molecules.…”
Section: Discussionmentioning
confidence: 90%
“…While MDSCs are known to inhibit CD8+ T cell proliferation, this study described an inverse association between CD14+ monocytes expressing VNN2 and glioma patient’s tumor grade potentially highlighting a role for VNN2 in less aggressive tumors [ 49 ]. In another study on metastatic renal cell carcinoma, VNN2 expression on monocytes and neutrophils was found to be correlated with poor prognostic outcomes [ 50 ]. Considering the limited work pertaining to VNN2′s significance in melanoma, mechanistic studies describing its effect on the tumor immune microenvironment are needed to establish practical recommendations.…”
Section: Discussionmentioning
confidence: 99%